USAHA KESEJAHTERAAN ANAK TERKAIT KESEHATAN DI KAMPUNG NELAYAN CILINCING: Child Welfare Efforts Related to Health in the Cilincing Fisherman’s Village - Nabila, Farra Mutiara; Retnowulandari, Wahyuni (AMICUS CURIAE, 2024)
Children's health has a significant impact on their growth and development. Every child has the right to receive welfare both in terms of health and growth and development, as stated in Article 2 paragraph (1) of Law Number 4 of 1979 concerning Child Welfare, which states, "Children have the right to welfare, care, upbringing, and guidance based on love, both in their family and in special care to grow and develop naturally." To fulfill children's health needs, health care efforts are needed, which are the responsibility of parents, the government, and society. However, in fact, there are many factors that influence the unfavorable situation and conditions in the Cilincing Fisherman's Village, which cause this not to be realized or not as it should be. The results of the research that has been carried out show that the most common illnesses suffered by children are acute respiratory infections (ARI) and diarrhea. This is due to the poor environmental conditions in the Cilincing Fisherman's Village, there are no septic tanks, and there are still many parents who underestimate the health of their children there.